The Impacts of Reducing Renewable Energy Subsidies on China's Energy Transition by Using a Hybrid Dynamic Computable General Equilibrium Model - Guo, Zhengquan; Zhang, Xingping; Feng, Sida; Zhang, Haonan (Frontiers in Energy Research, 2020)
This paper develops a hybrid computable general equilibrium model to explore the impacts of reducing renewable energy subsidies on China's energy transition in various scenarios. The results of the benchmark scenario indicate that China can realize its regulatory goals in energy consumption and structure and carbon emission intensity in 2030. This paper sets various policy scenarios to simulate the impacts of reducing renewable subsidies between 2021 and 2030. The analytical results of the scenarios indicate that the government's 2030 target for total energy and natural gas consumption and carbon emission intensity can be achieved. However, the target for non-fossil energy is hard to fulfill when the renewable energy subsidy is reduced. The empirical results also indicate that a moderate renewable energy subsidy associated with significant technical progress in renewable energy is a crucial way for China to fulfill government targets and energy transition in 2030.